EVALUASI PEMBELAJARAN SEJARAH BERBASIS UNIT KEGIATAN BELAJAR MANDIRI (UKBM) DIMASA PANDEMI COVID-19 - Hasan, Zainul (Universitas Negeri Malang, 2022)
In 2017, schools that have implemented the SKS were given a task by the government to implement learning based on the Independent Learning Activity Unit (UKBM). The policy regarding the implementation of UKBM is on a national scale and one of the regions that implements this system is Malang City, because quite a number of schools have implemented the Semester Credit System (SKS). One of the schools that implements the Semester Credit System is SMAN 1 Malang. Learning conditions have then changed since the COVID-19 pandemic hit in March 2020. Learning activities that were originally carried out directly have changed online so it needs to be evaluated considering a program that is relatively new and new conditions. Evaluation of the learning process of Indonesian history and the history of specialization in this study uses the Context, Input, Process and Product (CIPP) model. Research activities are carried out with a qualitative approach which includes several data collection methods such as observation, interviews and documentation. The results of the Process evaluation showed that the Indonesian History subject was given the title